1979
DOI: 10.1073/pnas.76.5.2094
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and electronic structure of oxyhemocyanin: spectral and chemical correlations to met apo, half met, met, and dimer active sites.

Abstract: The chemical and spectral properties of a series of hemocyanin derivatives were systematically compared to provide insight into the geometric and electronic structure of the oxyhemocyanin active site. The binuclear copper site is characterized as two tetragonal Cu(II) Oxygen binds as peroxide (1) to the active site in oxyhemocyanin (2) in the ratio of 1 02:2 Cu and it is generally agreed that the two coppers are in the +2 oxidation state, although a Cu(I)Cu(III) active site has recently been proposed (3). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
5

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 18 publications
2
60
0
5
Order By: Relevance
“…In addition, the cupric ions must be strongly antiferromagnetically coupled by the bound peroxide, since oxygenated hemocyanins are EPR silent (Dooley et al, 1978). Based on these data several models for the oxygenated dinuclear copper site in hemocyanin have been proposed (Eickman et al, 1979;Maddaluno & Giessner-Prettre, 1991;Ross & Solomon, 1991).…”
Section: B Hazes Et Almentioning
confidence: 99%
“…In addition, the cupric ions must be strongly antiferromagnetically coupled by the bound peroxide, since oxygenated hemocyanins are EPR silent (Dooley et al, 1978). Based on these data several models for the oxygenated dinuclear copper site in hemocyanin have been proposed (Eickman et al, 1979;Maddaluno & Giessner-Prettre, 1991;Ross & Solomon, 1991).…”
Section: B Hazes Et Almentioning
confidence: 99%
“…The theme of this talk will be to first develop our chemical-spectroscopic approach [1,2,3] for one mollusc hemocyanin in order to elucidate the unique spectroscopic features associated with its coupled binuclear copper active site. These features will then be used to generate a "spectroscopically effective" picture [3] of this site.…”
Section: Introductionmentioning
confidence: 99%
“…1 is reasonably well defined on the basis ofour chemical, spectral, and theoretical studies (11,12) of the series of derivatives shown in this figure, as well as resonance Raman studies, which indicated (19) the peroxide oxidation state of the bound dioxygen, and extended x-ray absorption fine structure (EX-AFS) analysis, which gave a Cu-Cu distance of 3.67 A (20) or 3.55 A (21). Cu(I) has a tendency toward lower coordination numbers, softer ligands, and a geometry based on ligand-ligand replusion (rather than unpaired d electron effects) relative to Cu(II).…”
mentioning
confidence: 99%